In silico analysis of a disease-causing mutation in PCDH15 gene in a consanguineous Pakistani family with Usher phenotype - Saleha, Shamim (Int J Ophthalmol, 2016)
AIM: To map Usher phenotype in a consanguineous Pakistani family and identify disease-associated mutation in a causative gene to establish phenotype-genotype correlation. METHODS: A consanguineous Pakistani family in which Usher phenotype was segregating as an autosomal recessive trait was ascertained. On the basis of results of clinical investigations of affected members of this family disease was diagnosed as Usher syndrome (USH). To identify the locus responsible for the Usher phenotype in this family, genomic DNA from blood sample of each individual was genotyped using microsatellite Short Tandem Repeat (STR) markers for the known Usher syndrome loci. Then direct sequencing was performed to find out disease associated mutations in the candidate gene. RESULTS: By genetic linkage analysis, the USH phenotype of this family was mapped to PCDH15 locus on chromosome 10q21.1. Three different point mutations in exon 11 of PCDH15 were identified and one of them, c.1304A>C was found to be segregating with the disease phenotype in Pakistani family with Usher phenotype. This, c.1304A>C transversion mutation predicts an amino-acid substitution of aspartic acid with an alanine at residue number 435 (p.D435A) of its protein product. Moreover, in silico analysis revealed conservation of aspartic acid at position 435 and predicated this change as pathogenic. CONCLUSION: The identification of c.1304A>C pathogenic mutation in PCDH15 gene and its association with Usher syndrome in a consanguineous Pakistani family is the first example of a missense mutation of PCDH15 causing USH1 phenotype. In previous reports, it was hypothesized that severe mutations such as truncated protein of PCDH15 led to the Usher I phenotype and that missense variants are mainly responsible for non-syndromic hearing impairment.